Treatment of Paediatric Supra Condylar Fracture Humerus (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: One of the most frequent elbow fractures in childhood, is supracondylar fracture whichrequires rapid diagnosis and treatment. It is usually associated with neurovascular, functional problems and deformity.Objectives: To assess demographic, clinical features and treatment outcomes of the patients who underwent closed reduction and splinting, stabilization by percutaneous pinning or Open Reduction and Internal Fixation(ORIF).Materials and Methods: This retrospective study was conducted in the department of orthopedic surgery, CMH, Bogura from June 2017 to December 2018. The inclusion criteria was Gartland type I,II,III fracture who attended in emergency and casualty, between 2 to 13 years of age. Total 40 patients with the mean age 7.5 years were included in the study group.Results: All were closed fractures, 2flexion and 38 extension type. Two (5%) Gartland type I, 24(60%) and 14(35%) had type II and III fracture respectively. 2(5%) were treated by cast immobilization,8(20%)of type llby closed reduction & splinting, 22(55%) and 8(20%) of type ll&lll by crossed k-wire or by ORIF respectively. According to Flynn’s criteria our study shows 33(82.5%) excellent, 4(10%) good, 2(5%) fair and 1(2.5%) poor outcome.4(10%) had ulnar nerve neuropraxia, 1(2.5%) elbow stiffness,1(2.5%) cubitusvarus, 2(5%) experienced superficial pin tract infection.Conclusion: Management of supracondylar fracture should be decided according to patient’s age, fracture pattern and deformity status. Closed reduction and stabilization by percutaneous wiring provides an effective and safe treatment, when failed, open fractures or associated neurovascular complications ORIF should be preferred.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 171-174